Effectiveness of Cordyceps fumosorosea wettable powder formulation against Metisa plana (Walker) and its side effects on Elaeidobius kamerunicus in oil palm plantation - Nasir, Ashraf Arif; Syarif, Nurul Yaqin; Omar, Dzolkhifli; Asib, Norhayu (Pesticide Science Society of Japan, 2023)
Development of mycoinsecticides with Cordyceps fumosorosea as an active ingredient is established as an alternate way to control the Metisa plana population while reducing chemical insecticide dependence. Three mycoinsecticide formulations (SS6, SS7, and SS8) with dispersing and wetting agents were developed as wettable powder formulations in this trial. SS8 demonstrated the best wettability, suspensibility, and dispersibility with viability at 107 (CFU)/mL even after three months of storage. However, SS7 developed with C. fumosorosea as an active ingredient was found to effectively reduce the bagworm population by more than 95. The application of all mycoinsecticide formulations in the infested oil palm area was able to reduce the M. plana population by more than 95, 30DAT. The formulations also show no significant increase in mortality of the oil palm pollinator, Elaeidobius kamerunicus. This finding indicates that the C. fumosorosea tested has potential for managing bagworms without harming pollinators on oil palm plantations.